Disparitas Dan Pola Spesialisasi Tenaga Kerja Industri Regional 1993 – 1996 Dan Prospek Pelaksanaan Otonomi - Suharto Suharto (Universitas Islam Indonesia, 2002)
This study explores the trend of regional disparity, specialisation, and concentration of manufacturing industry employment in Indonesia by province and sub-sector. The focus of this study is large and Medium (L-M) firm of manufacture industry.This study used industrial survey data from BPS 1993-1996. The main data are the sum of labor at large and medium manufacture industry. The tools of analysis consist of theil entropy index, Regional Specialisation index, regional gini coefficient, and locational gini coefficient.Based on analysis result showed that regional inequality in Indonesia manufacture employment relatively high, compare with international inequality. The other finding that disparity by province and the main island tend stable. Generally, the distribution of regional manufacture industry employment is not different (matches) with the overall ditribution (national). With exception at wood (ISIC 33) and Textile (ISIC 32) sub-sector, manufacture industry employment relatively distrubuted.Keywords: Disparity, Theil Index, Specialisation, Regional Gini Coefficient, and Locational Gini Coefficient.